Coated catalyst for methane oxygen-free aromatization and preparation method and application thereof
Through the combination of carburizing treatment and oxide coating, a core-shell type coating catalyst is formed, which solves the problem of metal-based molecular sieve catalyst migration and carbon deposits at high temperatures, and significantly improves the stability and reactivity of the catalyst.
Patent Information
- Application Number
- CN202411707253.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Metal-based molecular sieve catalysts are prone to migration of metal species and formation of metal carbides and coke at high temperatures, resulting in pore blockage and loss of active sites, reducing the reaction performance and stability of the catalyst.
By carburizing the molecular sieve catalyst supported by metal oxide, a molecular sieve supported by metal carbide is formed, and an oxide coating layer is formed on its surface to form a core-shell type coating catalyst.
It effectively improves the stability of metal species in the molecular sieve pores, reduces carbon deposits, extends the service life of the catalyst, and significantly improves the anti-inactivation ability and reaction activity of the catalyst.
Smart Images

Figure CN119186633B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a coated catalyst for methane oxygen-free aromatization and a preparation method and application thereof. Background Art
[0002] Methane aromatization (MDA) is a chemical reaction that converts methane directly into aromatics and hydrogen, usually at high temperatures of 700 to 800°C. This process is considered an effective way to achieve the economic conversion of natural gas atoms because it can efficiently convert methane with low economic value into high-value-added aromatic products.
[0003] In the oxygen-free aromatization reaction of methane, the selection and optimization of catalysts are crucial. Metal-based molecular sieve catalysts have attracted widespread attention due to their excellent performance in this reaction. The molecular sieve, as a carrier, provides a suitable acidic environment and pore structure, while the metal species is responsible for the activation and aromatization of methane. However, in practical applications, this type of catalyst faces many challenges. The main problem is that metal species can easily migrate from the pores of the molecular sieve to the surface of the catalyst at high temperatures to form metal carbides and generate coke (carbon deposition), which will lead to pore blockage and loss of active sites, thereby reducing the reaction performance of the catalyst and ultimately leading to catalyst deactivation.
[0004] In order to improve the anti-carbon deposition performance of metal-based molecular sieve catalysts, the methods currently adopted include alkaline etching treatment, incorporation of oxygen carriers, introduction of second metal sequential loading, etc. Although these methods can inhibit carbon deposition to a certain extent, they cannot fundamentally prevent the formation of carbon deposition, especially during long-term use, the activity of the catalyst will decrease significantly. In addition, by coating the molecular sieve carrier on the surface to form a core-shell molecular sieve carrier, the anti-carbon deposition performance and catalytic stability of the catalyst can be improved. However, the current coating method has the problems of complex preparation process, the need to completely remove the acidic sites on the outer surface, and high process requirements. Summary of the invention
[0005] In view of this, the primary purpose of the present invention is to provide a coated catalyst for oxygen-free aromatization of methane, which improves the stability of metal species in the pores of the molecular sieve through carburizing treatment, and at the same time forms a coating layer on the catalyst surface to reduce carbon deposition, thereby achieving effective control of metal species migration and carbon deposition inhibition, thereby improving the stability and reaction activity of the catalyst.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention provides a coated catalyst for methane oxygen-free aromatization, comprising a core portion and a shell portion coated on the surface of the core portion; wherein the core portion is a molecular sieve loaded with metal carbides, and the shell portion is an oxide.
[0008] The second aspect of the present invention provides a method for preparing a coated catalyst for methane aromatization without oxygen, the preparation method comprising the following steps:
[0009] Preparation of metal oxide-loaded molecular sieve catalysts;
[0010] Carburizing the metal oxide-loaded molecular sieve catalyst to obtain a metal carbide-loaded molecular sieve catalyst;
[0011] A coating layer is formed on the surface of the molecular sieve catalyst loaded with metal carbides to obtain a core-shell coated catalyst.
[0012] The third aspect of the present invention provides the use of a coated catalyst in an oxygen-free aromatization reaction of methane.
[0013] Beneficial effects of the present invention:
[0014] The coated catalyst in the present invention combines carburizing treatment and shell coating in a synergistic manner. Specifically, the active metal carbide obtained by carburizing treatment is loaded in the molecular sieve pores. The carburizing treatment ensures that the metal species are uniformly dispersed in the form of metal carbides in the molecular sieve pores, effectively improving the stability and anti-sintering performance of the active sites, thereby preventing the migration and loss of metal species under high temperature conditions. At the same time, as the coating layer of the shell, on the one hand, it provides an additional protective barrier for the active core, effectively isolates the metal species and the reaction gas, and significantly reduces the formation of carbon deposits; on the other hand, it controls the transfer of reactants by selective aperture, and improves the selectivity and yield of aromatics. In general, the present invention greatly enhances the durability of the catalyst and the stability of high temperature reaction through the synergy of carburizing treatment and shell coating, significantly prolongs the service life of the catalyst, and enables the catalyst to maintain a high activity after a long reaction, showing excellent anti-deactivation ability.
[0015] The coated catalyst of the present invention can significantly improve the conversion rate of methane oxygen-free aromatization reaction, which is a significant improvement. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is an optical photograph of catalyst A after carburizing at 700°C for 1 hour in Example 1 ( Figure 1 a) and catalyst A at 400℃ and 500℃ for 1h, and the obtained catalyst D ( Figure 1 b) and catalyst E ( Figure 1 c) Optical photograph.
[0017] Figure 2 Catalyst D was decarbonized at 400℃ for 12h ( Figure 2 a) and decarbonization at 400℃ for 24h ( Figure 2 b) Optical photograph after.
[0018] Figure 3 For fresh Mo2C ( Figure 3 a) and Mo2C after calcination at 400℃ in a muffle furnace for 10h ( Figure 3 b) Optical photograph.
[0019] Figure 4 Catalyst A ( Figure 4 a), Catalyst A was carburized according to the process in Example 1 ( Figure 4 b) Figure 4 The catalyst in b was kept in CO2 at 900℃ for 1h ( Figure 4 c) and Figure 4 After the quartz tube in c was treated with air for 1 h ( Figure 4 d) Optical photograph.
[0020] Figure 5 Catalyst F before removing carbon deposits ( Figure 5 a) and after removing carbon deposits ( Figure 5 b) Optical photograph.
[0021] Figure 6 Transmission electron microscopy (TEM) image of catalyst C (Mo2C / ZSM-5@ZSM-5).
[0022] Figure 7 X-ray diffraction results (XRD) of catalyst C (Mo2C / ZSM-5@ZSM-5), catalyst A (Mo / ZSM-5) and catalyst G (Mo / ZSM-5@ZSM-5).
[0023] Figure 8 Thermogravimetric curves (TG analysis) of catalyst C (Mo2C / ZSM-5@ZSM-5), catalyst A (Mo / ZSM-5) and catalyst G (Mo / ZSM-5@ZSM-5).
[0024] Fig. 9 The catalyst C (Mo2C / ZSM-5@ZSM-5) was used for the methane dehydrogenation aromatization reaction in the absence of oxygen for 4.5 h ( Fig. 9 a) and catalyst A (Mo / ZSM-5) for 1 h ( Fig. 9 b) Optical photograph after.
[0025] Fig.10is the conversion rate of catalyst C (Mo2C / ZSM-5@ZSM-5), catalyst A (Mo / ZSM-5) and catalyst G (Mo / ZSM-5@ZSM-5) in the oxygen-free dehydrogenation aromatization reaction of methane. DETAILED DESCRIPTION
[0026] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0028] <Coated Catalyst>
[0029] In the present invention, the coated catalyst for methane aromatization without oxygen is a core-shell catalyst having a core portion and a shell portion coated on the surface of the core portion.
[0030] The core part is a molecular sieve loaded with metal carbides, and the shell part is an oxide.
[0031] Since the core of the coated catalyst in the present invention is a molecular sieve loaded with metal carbides and the shell is an oxide, the problems of metal species loss and easy carbon deposition in traditional metal-based molecular sieve catalysts can be reduced, thereby improving the stability and life of the catalyst.
[0032] The "methane oxygen-free aromatization" described in this article refers to a catalytic process that directly converts methane into aromatics and hydrogen, which usually requires high temperature conditions (around 700-800°C).
[0033] The "molecular sieve" described herein refers to an inorganic crystalline material with a regular and uniform pore structure, usually composed of aluminosilicates, also known as synthetic zeolites or foamed zeolites. In the catalyst used for methane oxygen-free aromatization, the molecular sieve is usually used as a carrier for loading active metal species. In the present invention, the molecular sieve can be a common molecular sieve carrier used in methane oxygen-free aromatization catalysts, and specific examples include but are not limited to at least one of ZSM-5, ZSM-11, MCM-22, MCM-49, and MCM-56.
[0034] The "metal" mentioned herein refers to a metal species conventionally used in methane oxygen-free aromatization catalysts, for example, it may be at least one of molybdenum (Mo), gallium (Ga), zinc (Zn), manganese (Mn), tungsten (W), chromium (Cr), cobalt (Co), and iron (Fe), but is not limited thereto.
[0035] The "metal carbide" mentioned herein is a compound composed of the metal element mentioned above and the carbon element, and in this case is an active metal carbide obtained by carburizing the oxide of the metal element mentioned above.
[0036] The "oxide" as the shell part in this article is a class of oxygen-containing binary compounds, which as a coating material should have: ① thermal stability: it can maintain its structure and performance under the high temperature reaction conditions of methane oxygen-free aromatization, and will not degrade or modify during the reaction process; ② chemical inertness: that is, it will not react with the core catalyst and the external reaction gas, and can effectively isolate the active sites of the catalyst and the reaction gas, reduce the direct contact of the reactants with the active sites on the catalyst surface, thereby inhibiting the formation of carbon deposits; ③ pore size and specific surface area: appropriate pore size and specific surface area can promote the diffusion and catalytic reaction of the reactants, and will not affect the activity of the catalyst; ④ compatibility: it can be compatible with the metal active components in the catalyst and maintain the activity of the catalyst during the reaction. In the present invention, oxides that can meet the above conditions or requirements can be applied to the present invention, and specific examples that can be mentioned include one or more of SiO2, Al2O3, TiO2, and MgO, but are not limited to this. Preferably, it can be a composite of two or more oxides, so as to better improve the performance of the catalyst and improve the efficiency of the methane oxygen-free aromatization reaction to achieve the best catalytic effect.
[0037] In the present invention, each component in the coated catalyst can be determined by experiments based on methods known in the art. In some specific implementation cases, the metal carbide accounts for 5~15wt%, the molecular sieve accounts for 60~85wt%, and the oxide accounts for 5~20wt%.
[0038] In the present invention, there is no particular limitation on the particle size of the core and the thickness of the shell. A suitable coated catalyst can be prepared according to the needs by the preparation method described later. Preferably, the particle size of the core is 160-200 nm, and the thickness of the shell is 30-70 nm.
[0039] <Method for preparing coated catalyst>
[0040] The preparation method of the coated catalyst in the present invention is not particularly limited, and the preparation method known or commonly used in the art can be applied, which mainly includes: first preparing a molecular sieve catalyst loaded with metal oxides; then carburizing; and finally forming a coating layer.
[0041] In some specific implementation cases of the present invention, the preparation of the coated catalyst comprises at least the following steps:
[0042] S1. preparing a molecular sieve catalyst loaded with metal oxide;
[0043] S2, performing carburizing treatment on the molecular sieve catalyst loaded with metal oxide to obtain a molecular sieve catalyst loaded with metal carbide;
[0044] S3, forming a coating layer on the surface of the molecular sieve catalyst loaded with metal carbides to obtain a core-shell coated catalyst.
[0045] Among them, the method for preparing the metal oxide molecular sieve catalyst in step S1 is not particularly limited, and the method known or commonly used in the art can be adopted, as long as the metal species can be evenly loaded on the molecular sieve carrier to ensure the activity and selectivity of the catalyst. For example, in some specific implementation cases of the present invention, the wet impregnation method is adopted for preparation.
[0046] The wet impregnation method mainly includes the steps of preparing a metal oxide precursor solution using a metal salt, adding a molecular sieve thereto, and after sufficient impregnation, drying and calcining to obtain a molecular sieve catalyst loaded with a metal oxide. The specific reaction conditions and parameters can be adjusted based on methods or conditions known in the art or determined by experiments, and will not be elaborated here one by one.
[0047] In the present invention, the carburizing treatment in step S2 is one of the key steps, which specifically includes the following steps:
[0048] The metal oxide-loaded molecular sieve catalyst is heated to 650° C. to 700° C. in an inert atmosphere, switched to CH4, and kept warm to allow the metal oxide to transform into an active metal carbide;
[0049] The temperature is raised to 700°C~750°C in an inert atmosphere and kept at this temperature for 0.5h~1h; the temperature is switched to a decarbonizing gas and raised to 750°C~800°C to remove carbon deposits and obtain a molecular sieve catalyst loaded with metal carbides.
[0050] In the present invention, (1) methane (CH4) is used as the carburizing gas. The CH bond energy in the methane molecule is high, and it can be decomposed at a lower temperature and stably generate metal carbides, which helps to effectively control the carburization rate and reduce excessive carbon deposition; in addition, the high carbon source concentration of methane accelerates the carburization reaction rate and can improve the efficiency of carburization. (2) In the present invention, a specially designed temperature control strategy is used in the carburizing treatment, and the temperature is increased and maintained in stages. Specifically, the carbonization of the metal oxide is initially achieved at 650~700℃ (923~973K), and then the formation of the metal carbide is further stabilized at 700~750℃ (973~1023K). This multi-stage temperature control strategy effectively controls the carburization rate, reduces ineffective carbon deposition, and protects the integrity of the pore structure of the molecular sieve. (3) The present invention adds a decarbonization step after carburizing. After carburizing, the catalyst is heated to 750-800°C in an inert atmosphere, and then the decarbonization gas is introduced to reduce the coverage of carbon deposits on the surface of active metal carbides, ensuring that the excess carbon generated during the carburizing treatment can be effectively removed, avoiding the blockage of active sites by excessive carbon deposition, and improving the activity and anti-carbon deposition performance of the catalyst. (4) After the decarbonization is completed, the present invention directly cools to room temperature in an inert atmosphere to further avoid the coverage of carbon deposits, ensure the cleanliness of the active sites on the catalyst surface, and provide higher activity and stability for the subsequent use of the catalyst.
[0051] In general, the present invention avoids the problem of ineffective carbon deposition through gas selection, temperature control and carbon removal treatment in carburizing treatment, greatly reduces carbon deposition on the catalyst surface, keeps the active sites clean, improves the carbon deposition resistance and stability of the catalyst, and effectively prolongs the active life of the catalyst. Wherein, the gas flow rate of CH4 is 10sccm~20sccm; and / or, the holding time is 15~40min.
[0052] During the carburizing treatment, a decarbonizing gas is used to remove carbon deposits. In the present invention, the decarbonizing gas used is a mixture of H2 and an inactive gas. The H2 in the decarbonizing gas can selectively reduce the surface carbon, so that the active metal carbide obtains a clean surface and reduces the coverage of carbon deposits. Among them, the volume proportion of H2 in the decarbonizing gas is 5% to 20%. In the present invention, the inert atmosphere and the inactive gas have the same meaning, both of which refer to gases that will not participate in the reaction, that is, gases that are inert to the catalyst gas or the reaction materials, specifically nitrogen, and can also be rare gases such as helium, argon, etc. It can be understood that the treatment time of the decarbonizing gas can be adjusted or optimized according to the actual situation, preferably 3 to 6 hours.
[0053] It should be noted that the present invention also includes a sand grinding step after the carburizing treatment, by which the catalyst is refined to obtain small particles, thereby increasing its specific surface area, enhancing the reaction activity and catalytic performance. The small particle catalyst can provide more active sites, thereby helping to improve the reaction rate and catalytic efficiency.
[0054] Specifically, sand milling is to mix the catalyst and the dispersant and then sand mill them at a certain speed for a period of time. The dispersant used includes but is not limited to polyvinyl pyrrolidone PVP, polyvinyl alcohol PVA, sodium dodecylbenzene sulfonate SDS or polyvinyl acetate to provide good dispersibility and stability and effectively prevent the agglomeration of metal particles. The ratio of the dispersant to the catalyst can be adjusted as needed, preferably between 1: (10~20).
[0055] The speed and time of sand milling can be adjusted based on the type of catalyst and dispersant, generally between 200~2500rpm, preferably 1500~2500rpm. The sand milling time is generally 0.5~3h, preferably 0.5~1h, and is adjusted according to the size of the catalyst particles. Large particles require longer time. At the same time, it should be noted that sand milling for a period of time and then cooling for a period of time, alternating, for example, sand milling for 10 minutes and then cooling for 10 minutes, to ensure the sand milling effect.
[0056] In the present invention, step S3 is another key step for forming the coating layer. The method for forming the coating layer may be well known in the art, such as a sol-gel method, a hydrothermal method, a spraying method, a vapor deposition method or a liquid deposition method.
[0057] In some specific implementation cases of the invention, the method used to form the coating layer is the sol-gel method, that is, the carburized catalyst is added to a solution containing an oxide precursor, and a template is added at the same time, and the reaction is carried out at a certain speed for a period of time. Finally, after the hydrothermal reaction, the template and other organic matter can be removed.
[0058] The oxide precursor used varies according to the different oxides coated. For example, in some embodiments, the oxide is magnesium oxide (MgO), and the precursor used may be at least one of magnesium chloride (MgCl2), magnesium nitrate (Mg(NO3)2), and magnesium carbonate (MgCO3), but is not limited thereto. For example, if the oxide is titanium dioxide (TiO2), the precursor used may be at least one of tetraisopropyl titanate (TIPT), tetrabutyl titanate (TBT), titanium chloride (TiCl4), and titanate (such as Ti(OH)4). For example, if the oxide is silicon dioxide (SiO2), the precursor used may be at least one of sodium silicate (Na2SiO3), ammonium silicate ((NH4)2SiO3), and tetraethoxysilane (TEOS). For example, if the oxide is aluminum oxide (Al2O3), the precursor used may be at least one of aluminum chloride (AlCl3) and sodium aluminate as an aluminum source (NaAlO2), but is not limited to those described herein.
[0059] The template used can be an organic template, an inorganic template, a self-assembly template or a metal template commonly used in the art for preparing oxides, which differs according to the preparation method and the type of oxide formed. Specific examples of the organic template include, but are not limited to, tetrapropylammonium hydroxide (TPAOH), polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyetheramide (PEA), polymer micelles such as polyacrylic acid (PAA), etc. The inorganic template can be hydroxides and salts (such as sodium hydroxide (NaOH), aluminum hydroxide (Al(OH)3), silicates (such as hydrated sodium silicate), aluminates (such as sodium aluminate). The self-assembly templates include liposomes (such as phospholipids), micelles formed by self-assembly of surfactants, etc. The metal templates include metal nanoparticles (such as silver, gold, etc.), metal organic frameworks (MOFs), etc.
[0060] In addition, after the coating layer is formed, it is necessary to remove organic matter such as the template in the molecular sieve. Preferably, in some specific embodiments of the present invention, a mixed gas treatment of H2 and inert gas is used for better results, wherein the volume proportion of H2 is 5% to 20%. The inert gas has the same meaning as described above and will not be elaborated here.
[0061] The present invention also provides application of the coated catalyst in methane oxygen-free aromatization reaction.
[0062] The coated catalyst can greatly reduce the migration of metal species and avoid the formation of carbon deposits. After a long period of reaction, such as about 10 hours, it can still maintain a high catalytic activity, which has significant advantages.
[0063] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial channels.
[0064] Example 1
[0065] This embodiment provides a coated catalyst for methane oxygen-free aromatization reaction and a preparation method thereof, and the specific preparation steps are as follows:
[0066] 1. Preparation of Mo / ZSM-5 catalyst
[0067] (1) Prepare ammonia solution: Use 25% to 28% ammonia water and deionized water to dilute and prepare 0.15 mol / L ammonia solution.
[0068] (2) Preparation of metal precursor solution: Weigh 0.2208 g of ammonium heptamolybdate tetrahydrate into a 100 mL round-bottom flask. Use a pipette to transfer 20 mL of the ammonia solution prepared in step (1). Place the round-bottom flask containing the mixed solution in an ultrasonic cleaner and perform ultrasonic cleaning for 15 min until the solution becomes clear.
[0069] (3) Preparation of impregnation solution: Add 2.000 g of zeolite molecular sieve ZSM-5 (SiO2 / Al2O3=36) to the solution of step (2), and heat and stir in a water bath at 40°C at a speed of 500 r / min for 12 h.
[0070] (4) Drying and calcining: The impregnation solution in step (3) was transferred to a beaker, the water bath temperature was increased to 80°C, and the mixture was stirred until completely evaporated, and then the beaker was transferred from the water bath to an oven at 120°C for drying for 24 h; finally, the temperature was increased from room temperature to 500°C at a heating rate of 1°C / min in an air atmosphere, and then calcined at 500°C for 6 h; cooled to room temperature, pressed into tablets, crushed, and sieved to obtain 40-80 mesh particles, thereby obtaining a catalyst Mo / ZSM-5 for methane oxygen-free aromatization reaction, which includes active components of molybdenum oxide MoO3 and ZSM-5 molecular sieve, and is referred to as catalyst A in this embodiment.
[0071] 2. Preparation of catalyst Mo2C / ZSM-5
[0072] (1) Take 0.2 g of catalyst A and put it into a quartz tube with a diameter of 0.8 mm and a length of 45 cm. Then put the quartz tube containing catalyst A into a fixed bed.
[0073] (2) Raise the temperature to 650°C in an inert Ar atmosphere, switch to 10 sccm CH4, and keep warm for 30 min.
[0074] (3) The temperature was raised to 700 °C in an inert atmosphere of Ar and kept at this temperature for 1 h. The carbon removal gas (10% H2 / Ar) was switched and the temperature was raised to 800 °C and kept at this temperature for 3 h to remove the carbon deposits and obtain the catalyst Mo2C / ZSM-5.
[0075] (4) Add 1 g Mo2C / ZSM-5, 2 g polyvinylpyrrolidone (PVP), and 200 mL deionized water into a sand mill in sequence, and sand grind at 2500 rpm for 50 min. Note that the sand milling should be cooled for 10 min after 10 min of grinding to refine the molecular sieve particles and obtain small particles of Mo2C / ZSM-5, which include active components Mo2C and ZSM-5 molecular sieve, and are recorded as catalyst B in this example.
[0076] 3. Preparation of coated catalyst Mo2C / ZSM-5@ZSM-5
[0077] (1) Add 9.5 mL of deionized water, 2.438 mL of tetraethoxysilane as a silicon source (TEOS), 18 mg of sodium aluminate as an aluminum source (NaAlO2), and 1.485 mL of tetrapropylammonium hydroxide as a template (TPAOH) into a round-bottom flask, stir at 400-600 r / min at room temperature, and hydrolyze for 6 h to obtain a ZSM-5 precursor.
[0078] (2) The suspension of catalyst B after sand grinding was allowed to stand for 2 h, and 38 ml of the upper layer of the suspension was added to 0.2 g of the ZSM-5 precursor prepared in step (1); the reaction was hydrothermally reacted in an autoclave (140 °C for 10 h), centrifuged, and dried at 110 °C for 8 h.
[0079] (3) The hydrothermal reaction product in step (2) was placed in a tubular furnace and treated at 800° C. for 6 h in 10% H 2 / Ar with 10 sccm to remove organic matter such as the template in the molecular sieve, thereby obtaining a coated catalyst Mo 2 C / ZSM-5@ZSM-5, which is referred to as catalyst C in this example.
[0080] Example 2
[0081] This embodiment provides another coated catalyst for methane aromatization reaction without oxygen and a preparation method thereof. The specific preparation steps are as follows:
[0082] 1. Preparation of Mo / ZSM-5 catalyst
[0083] Same as Example 1.
[0084] 2. Preparation of catalyst Mo2C / ZSM-5
[0085] (1) Take 0.2 g of catalyst A and put it into a quartz tube with a diameter of 0.8 mm and a length of 45 cm. Then put the quartz tube containing catalyst A into a fixed bed.
[0086] (2) Raise the temperature to 680°C in an inert Ar atmosphere, switch to 15 sccm CH4, and keep warm for 40 min.
[0087] (3) The temperature was raised to 720°C in an inert atmosphere of Ar and kept at this temperature for 50 min. The carbon removal gas (5% H2 / Ar) was switched and the temperature was raised to 780°C and kept at this temperature for 6 h to remove the carbon deposits and obtain the catalyst Mo2C / ZSM-5.
[0088] (4) Add 1 g Mo2C / ZSM-5, 2 g polyvinylpyrrolidone (PVP), and 200 mL deionized water into a sand mill in sequence, and sand grind at 2500 rpm for 50 min. Note that the sand milling should be cooled for 10 min after 10 min of grinding to refine the molecular sieve particles and obtain small particles of Mo2C / ZSM-5, which include active components Mo2C and ZSM-5 molecular sieve, and are recorded as catalyst B in this example.
[0089] 3. Preparation of coated catalyst Mo2C / ZSM-5@ZSM-5
[0090] Same as Example 1.
[0091] Example 3
[0092] This embodiment provides another coated catalyst for methane aromatization reaction without oxygen and a preparation method thereof. The specific preparation steps are as follows:
[0093] 1. Preparation of Mo / ZSM-5 catalyst
[0094] Same as Example 1.
[0095] 2. Preparation of catalyst Mo2C / ZSM-5
[0096] (1) Take 0.2 g of catalyst A and put it into a quartz tube with a diameter of 0.8 mm and a length of 45 cm. Then put the quartz tube containing catalyst A into a fixed bed.
[0097] (2) Raise the temperature to 700°C in an inert Ar atmosphere, switch to 20 sccm CH4, and keep warm for 15 min.
[0098] (3) The temperature was raised to 750 °C in an inert atmosphere of Ar and kept at this temperature for 30 min. The carbon removal gas (20% H2 / Ar) was switched and the temperature was raised to 750 °C and kept at this temperature for 4 h to remove the carbon deposits and obtain the catalyst Mo2C / ZSM-5.
[0099] (4) Add 1 g Mo2C / ZSM-5, 2 g polyvinyl alcohol (PVA), and 200 mL deionized water into a sand mill in sequence, and sand grind at 2000 rpm for 1.5 h. Note that the sand milling should be cooled for 10 min after 10 min of grinding to refine the molecular sieve particles and obtain small particles of Mo2C / ZSM-5, which include active components Mo2C and ZSM-5 molecular sieve, and are recorded as catalyst B in this example.
[0100] 3. Preparation of coated catalyst Mo2C / ZSM-5@ZSM-5
[0101] Same as Example 1.
[0102] Example 4
[0103] This embodiment provides another coated catalyst for methane aromatization reaction without oxygen and a preparation method thereof, which adopts the same implementation as that of Example 1, with the only difference being that the coating material of the shell is MgO.
[0104] Example 5
[0105] This embodiment provides another coated catalyst for methane oxygen-free aromatization reaction and a preparation method thereof, which adopts the same implementation as that of Example 1, with the only difference being that the coating material of the shell is TiO2.
[0106] Since byproduct carbon deposits are generated during the process of preparing catalyst B by carburizing catalyst A, a certain method is required to remove the carbon deposits. In the present invention, reducing gases such as H2 and inactive gases are used for removal, and comparative examples 1 and 2 using different carbon removal gases are designed for comparison.
[0107] Comparative Example 1
[0108] In this comparative example, air is used as the decarburizing gas, and the specific carburizing treatment steps are as follows:
[0109] (1) Catalyst A is placed in a quartz tube with a diameter of 0.8 mm and a length of 45 cm, and the quartz tube containing catalyst A is placed in a fixed bed.
[0110] (2) Raise the temperature to 650°C in an inert Ar atmosphere, switch to 10 sccm CH4, and keep warm for 30 min.
[0111] (3) The temperature was raised to 700°C in an inert atmosphere of Ar and kept at this temperature for 1 hour. The temperature was then switched to air to remove carbon deposits and the temperature was raised to 400°C and 500°C respectively and kept at this temperature for 1 hour to obtain catalysts D and E (states as shown in FIG. Figure 1 The color change of the catalysts involves the oxidation of two species: carbon deposits and molybdenum carbide. It can be seen that catalyst D is not completely oxidized and catalyst E is over-oxidized.
[0112] (4) Catalyst D was subjected to decarbonization treatment at 400 °C for different holding times (12 h and 24 h). Catalyst D was over-oxidized (states such as Figure 2 as shown).
[0113] (5) Activated carbon was treated in an oven at 100°C for 1 hour. 50 mg of activated carbon was taken before calcination and calcined in a muffle furnace at 400°C for 1 hour. After calcination, 36 mg was weighed. Calcination was continued at 500°C for 1 hour and 2 mg was weighed. Air calcination can remove carbon deposits, but it cannot guarantee that Mo2C will not be oxidized. Therefore, Mo2C calcination was performed later to verify whether oxidation would occur.
[0114] (6) Mo2C was treated in an oven at 100℃ for 1h. 50mg of Mo2C was taken before calcination and calcined in a muffle furnace at 400℃ for 10h. After calcination, 50mg was weighed and the weight was 45mg. The color and weight changes can prove that Mo2C will oxidize under this condition (state such as Figure 3 as shown).
[0115] It can be concluded from Example 1 that although air as a carbon removal gas can remove carbon deposits, under this condition, Mo2C will be oxidized.
[0116] Comparative Example 2
[0117] In this comparative example, calcination was performed in CO2 to determine the oxidation of the carburized catalyst A in CO2. The specific steps are as follows:
[0118] (1) CO2 can react with carbon deposits at 900℃ (CO2+C=CO). Take 50mg of activated carbon and put it into a tubular furnace. Keep it at 900℃ in a CO2 atmosphere for 1h. After the reaction, weigh 22g.
[0119] (2) After carburizing the catalyst A in Example 1, the Ar atmosphere was raised to 900°C and then switched to CO2 and maintained at 900°C for 1 hour.
[0120] (3) After CO2 treatment, a large amount of black matter was present on the tube wall. When air was introduced to calcine the empty tube, the black deposits on the tube wall disappeared (state such as Figure 4 As shown in the figure), it proves that it is not Mo2C species but carbon deposits, which means that carbon deposits cannot be completely treated in CO2 atmosphere.
[0121] Comparative Example 3
[0122] This comparative example provides a catalyst for methane aromatization reaction without oxygen, which adopts the same implementation as Example 1, except that: no coating is performed.
[0123] The specific preparation steps of the catalyst for methane oxygen-free aromatization reaction are as follows:
[0124] 1. Preparation of Mo / ZSM-5 catalyst
[0125] Same as Example 1.
[0126] 2. Preparation of catalyst Mo2C / ZSM-5
[0127] (1) Take 0.2 g of catalyst A and put it into a quartz tube with a diameter of 0.8 mm and a length of 45 cm. Then put the quartz tube containing catalyst A into a fixed bed.
[0128] (2) Raise the temperature to 650°C in an inert Ar atmosphere, switch to 10 sccm CH4, and keep warm for 30 min.
[0129] (3) The temperature was raised to 700 °C in an inert atmosphere of Ar and kept at this temperature for 1 h. The carbon removal gas (10% H2 / Ar) was switched and the temperature was raised to 800 °C and kept at this temperature for 3 h to remove the carbon deposits and obtain the catalyst Mo2C / ZSM-5, which was recorded as catalyst F.
[0130] Figure 5 The state diagram of catalyst F before and after carbon deposits were removed by using carbon removal gas containing H2 is shown. It can be seen that the use of carbon removal gas containing H2 did not cause the color of the catalyst to turn white, indicating that no excessive oxidation occurred, indicating that the use of carbon removal gas containing H2 can effectively maintain the original state of the catalyst while removing carbon; in addition, after H2 carbon removal, not only the problem of incomplete oxidation was avoided, but also no excess carbon residue appeared on the quartz tube wall, indicating that the use of carbon removal gas containing H2 can completely remove carbon deposits and ensure the clean state of the catalyst surface. In general, the carbon deposition problem on the catalyst surface can be effectively removed by using carbon removal gas containing H2, further ensuring the activity and long-term stability of the catalyst.
[0131] Comparative Example 4
[0132] This comparative example provides a catalyst for methane oxygen-free aromatization reaction, which adopts the same implementation as Example 1, except that no carburizing treatment is performed.
[0133] The specific preparation steps of the catalyst for methane oxygen-free aromatization reaction are as follows:
[0134] 1. Preparation of Mo / ZSM-5 catalyst
[0135] Same as Example 1.
[0136] It should be noted that the catalyst A should be sand-milled. The steps are as follows: 1 g of catalyst A, 2 g of polyvinyl alcohol (PVA), and 200 mL of deionized water are added to the sand mill in sequence, and sand-milled at 2000 rpm for 1.5 h. Note that the sand milling should be cooled for 10 min after 10 min to refine the molecular sieve particles and obtain small particles of catalyst A.
[0137] 2. Preparation of coated catalyst Mo / ZSM-5@ZSM-5
[0138] (1) Add 9.5 mL of deionized water, 2.438 mL of tetraethoxysilane as a silicon source (TEOS), 18 mg of sodium aluminate as an aluminum source (NaAlO2), and 1.485 mL of tetrapropylammonium hydroxide as a template (TPAOH) into a round-bottom flask, stir at 400-600 r / min at room temperature, and hydrolyze for 6 h to obtain a ZSM-5 precursor.
[0139] (2) The suspension of catalyst A after sand grinding was allowed to stand for 2 h, and 38 ml of the upper layer of the suspension was added to 0.2 g of the ZSM-5 precursor prepared in step (1); the reaction was hydrothermally reacted in an autoclave (140°C for 10 h), centrifuged, and dried at 110°C for 8 h.
[0140] (3) The hydrothermal reaction product in step (2) was placed in a tubular furnace and treated at 800° C. for 6 h in 10% H 2 / Ar with 10 sccm to remove organic matter such as the template agent in the molecular sieve, thereby obtaining a coated catalyst Mo / ZSM-5@ZSM-5, which is referred to as catalyst G in this example.
[0141] Structural characterization and performance testing
[0142] 1. Figure 6 The transmission electron microscopy characterization results of catalyst C (Mo2C / ZSM-5@ZSM-5) in Example 1 are shown in FIG. 1 , and it can be seen that catalyst C has a core and a shell, indicating that catalyst C is a core-shell structure. The size of the core is 180 nm, and the size of the shell is 50 nm.
[0143] 2. Figure 7 The X-ray diffraction results of catalyst C (Mo2C / ZSM-5@ZSM-5), catalyst A (Mo / ZSM-5) in Example 1 and catalyst G (Mo / ZSM-5@ZSM-5) in Comparative Example 4 are shown. It can be seen that the crystal structure of the molecular sieve of catalyst A (Mo / ZSM-5) remains stable before and after carburization treatment and before and after coating treatment, and no significant changes occur. This shows that the carburization process and coating process of the present invention will not damage the structural integrity of the molecular sieve, ensuring the integrity of the pore structure and acid sites of the carrier, thereby providing good stability and activity support for the catalyst.
[0144] 3. Figure 8The thermogravimetric curves of catalyst C (Mo2C / ZSM-5@ZSM-5), catalyst A (Mo / ZSM-5) in Example 1 and catalyst G (Mo / ZSM-5@ZSM-5) in Comparative Example 4 are shown. It can be seen that the weight loss in the temperature range of 300℃~600℃ is mainly attributed to the removal of carbon deposits in the pores of the molecular sieve; the mass loss of the catalyst in this temperature range reflects the process of decomposition and removal of carbon deposits formed during the reaction during heat treatment. For the coated Mo2C / ZSM-5@ZSM-5 catalyst, the thermogravimetric analysis results show that its carbon deposit amount is reduced by 1.5~1.8wt%. This shows that the design of the coating layer effectively prevents carbon from being deposited in the pores of the catalyst, thereby slowing down the rate of carbon deposition.
[0145] 4. Catalyst C (Mo2C / ZSM-5@ZSM-5), Catalyst A (Mo / ZSM-5) in Example 1 and Catalyst G (Mo / ZSM-5@ZSM-5) in Comparative Example 4 were used in methane dehydrogenation aromatization reaction respectively. The specific reaction conditions were: reaction temperature of 700°C, pressure of normal pressure, reaction gas of 10 sccm CH4, and space velocity of 1500-4000 ml·g cat -1 ·h -1 The test results are shown in Fig. 9 and Fig.10 .
[0146] It can be seen that the amount of carbon deposits on the coated catalyst prepared in the present invention is significantly reduced after the reaction, which significantly improves the anti-carbon deposition performance of the catalyst ( Fig. 9 ).
[0147] Further, through Fig.10 It can be seen that compared with catalyst A, the methane conversion rate of the core-shell catalyst C is increased by about 4%. Catalyst C still maintains a conversion rate of about 6% after 10 hours of reaction, while catalyst A and catalyst G only maintain a conversion rate of about 2%, indicating that the coated catalyst in the present invention has higher catalytic efficiency and reaction stability. It can be concluded that the reduction of carbon deposition not only improves the exposure degree of active sites on the catalyst surface, but also enhances its anti-carbon deposition ability, so that it can still maintain a high catalytic activity after long-term operation, and has better anti-carbon deposition performance and long-term stability in the methane oxygen-free dehydrogenation aromatization reaction, which significantly improves the life and practicality of the catalyst. In general, the coated catalyst in the present invention shows significant advantages in extending service life and maintaining efficient reaction performance, and is suitable for methane conversion under high temperature reaction conditions.
[0148] It should be noted that the present invention specifically describes the molybdenum-based molecular sieve catalyst as an example, but other conventional molecular sieve catalysts that can be used in the methane dehydrogenation aromatization reaction as metal species or carriers can achieve the effect or purpose of the present invention:
[0149] For example, the metal species may also be at least one of gallium (Ga), zinc (Zn), manganese (Mn), tungsten (W), chromium (Cr), cobalt (Co), and iron (Fe).
[0150] The molecular sieve carrier can also be at least one of ZSM-11, MCM-22, MCM-49, and MCM-56.
[0151] The coating layer can also be formed by a hydrothermal method, a spraying method, a vapor deposition method, a liquid deposition method, or the like.
[0152] The specific experimental conditions can be determined by those skilled in the art by known methods, which will not be elaborated here.
[0153] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0154] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a coated catalyst for methane aromatization without oxygen, characterized in that: The following steps are involved: The metal precursor solution is prepared by dissolving ammonium heptamolybdate tetrahydrate in an ammonia solution, and a molecular sieve is added thereto. After being fully impregnated, the solution is dried and calcined at 500° C. to prepare a molecular sieve catalyst loaded with metal oxides. The molecular sieve catalyst loaded with metal oxide is heated to 650°C in an inert atmosphere, switched to CH4, and kept warm so that the metal oxide is converted into active metal carbide; the temperature is raised to 700°C-750°C in an inert atmosphere, and kept warm for 0.5h-1h; the temperature is switched to decarbonizing gas, and the temperature is raised to 750°C-800°C to remove carbon deposits to obtain a molecular sieve catalyst loaded with metal carbide; the decarbonizing gas is a mixture of H2 and an inactive gas, wherein the volume proportion of H2 is 5%-20%; After sand grinding the molecular sieve catalyst loaded with metal carbide, the molecular sieve catalyst is added to an oxide precursor solution containing a template agent, stirred and subjected to hydrothermal reaction, and the product is treated with a mixture of H2 and an inactive gas at 800°C to remove the template agent in the molecular sieve, and a coating layer is formed on the surface of the molecular sieve catalyst loaded with metal carbide to obtain a core-shell coated catalyst; The coated catalyst comprises a core and a shell coated on the surface of the core; wherein the core is a molecular sieve loaded with metal carbides, the shell is an oxide, and the particle size of the core is between 160 and 200 nm.
2. The preparation method according to claim 1, characterized in that The molecular sieve is at least one of ZSM-5, ZSM-11, MCM-22, MCM-49, and MCM-56; And / or, the oxide is one or a composite of two or more of SiO2, Al2O3, TiO2, and MgO.
3. The preparation method according to claim 1, characterized in that: In the coated catalyst, the metal carbide accounts for 5-15wt%, the molecular sieve accounts for 60-85wt%, and the oxide accounts for 5-20wt%.
4. The preparation method according to claim 1, characterized in that: The metal precursor solution is formed by dissolving 0.2208 g of ammonium heptamolybdate tetrahydrate in 20 mL of 0.15 mol / L ammonia solution.
5. The preparation method according to claim 1, characterized in that: The CH4 gas flow rate is 10 sccm-20 sccm, and the insulation time is 15-40 min.
6. The preparation method according to claim 1, characterized in that: The inert gas is nitrogen, helium or argon; And / or, the treatment time of the decarbonizing gas is 3 to 6 hours.
7. Use of the coated catalyst prepared by the preparation method according to any one of claims 1 to 6 in the oxygen-free aromatization reaction of methane.
Citation Information
Patent Citations
Polyfunctional catalysts
US20200031735A1